Geniposidic acid inhibits OVA-induced asthma by suppressing allergic airway inflammation and regulating gut microbiota - Zheng, Yang; Gao, Dengyu; Xie, Hongyang; Geng, Huafeng (Frontiers in Immunology, 2025)
Asthma is a serious chronic inflammatory disease of the respiratory system. In this study, we aimed to explore the role of geniposidic acid (GPA) in ovalbumin (OVA)-induced asthma in mice and to clarify its underlying mechanism. The mice were divided into control group, OVA group, OVA+GPA (12.5, 25, 50 mg/kg) groups. Inflammatory mediators were measured by ELISA. Gut microbiota was detected by 16S RNA sequencing. The results demonstrated that GPA attenuated OVA-induced lung injury, inflammatory cell infiltration, and mucus hypersecretion. OVA-induced IL-4, IL-5, IL-13, and IgE production was also inhibited by GPA. IFN-γ production was increased by GPA. Furthermore, GPA inhibited OVA-induced NF-κB activation and increased Nrf2 expression. In addition, GPA alleviated the dysbiosis of gut microbiota induced by OVA. After GPA treatment, the diversity and abundance of intestinal microbiota in asthma mice increased. At the phylum level, GPA significantly reduced the relative abundance of Ligilactobacillus, Lachnospiraceae, Helicobacter, and Bacteroidales and significantly increased the relative abundance of Muribaculaceae and Muribaculum. In conclusion, GPA protect mice against OVA-induced asthma through suppressing inflammation and regulating gut microbiota.